Hsp90: a chaperone for protein kinases and hormone receptors - Toft, David (Henry Stewart Talks, 2007)
Chaperoning steroid receptors; the Hsp90 chaperoning machine, Hsp90 structure and function, Chaperoning protein kinases and other Hsp90 clients